Reproduction of Knowledge for Power: Critical Discourse Analysis of Scientific Articles and Speeches of Megeawati - Febi Putri Utami; Rustono Rustono; Bernadus Wahyudi Joko Santoso (Universitas Muhammadiyah Enrekang, 2023)
The inauguration of Megawati Soekarnoputri as an honorary professor at the Defense University of the Republic of Indonesia became a topic of conversation among the public because this was the first time this had happened in Indonesia. Megawati wrote a scientific work entitled